Attractiveness consumption, personality traits and sustainability: Construction and empirical application of evaluation indicators for attractive attributes of China-chic T-shirt products - Liu, Hongwen; Guo, Chunli; Zhang, Beibei (Frontiers in Psychology, 2022)
Background The rapid development of China’s cultural and creative industries has given cultural fashion products, represented by China-chic (国潮) T-shirts, vitality. In recent years, with the arrival of the era of design-led emotional sensory, products with attractive and qualia characteristics have become an important tool to attract consumers and create a competitive brand. Objective Therefore, this study aimed to build an evaluation index of the attractive attributes of China-chic T-shirt products from the perspective of attractive consumption to serve as an important basis for improving product development and thus promoting the sustainable development of China-chic T-shirt products. Methods Firstly, a three-level hierarchical model was established for the sustainable development of China-chic T-shirt products based on literature research. Secondly, through the evaluation grid method and factor analysis method, we extracted the attractive elements and factors associated with China-chic T-shirt products and established an objective evaluation index for the attractive attributes of China-chic T-shirt products. Twenty-five participants with different decision-making personalities tested three products with expert validity. The weights of the evaluation indexes of the attractive attributes of China-chic T-shirt products were evaluated using the fuzzy analytic hierarchy process. Finally, a two-factor mixed design ANOVA was conducted to check the practical value of the evaluation index of the attractive attributes of China-chic T-shirt products. Results The results show that the evaluation indexes of the attractive attributes of China-chic T-shirt products include 7 attractive factors, including the brand image feature, perceptual association feature, beauty feature, delicacy feature, creativity feature, engineering feature, and green feature, as well as 32 attractive elements. Through an empirical application analysis, it was found that the index has an excellent ability to differentiate between the attractive characteristics of different styles of products and test participants with different decision-making personalities.